Does chronic kidney disease improve the predictive value of the CHADS2 and CHA2DS2-VASc stroke stratification risk scores for atrial fibrillation? - Roldán, Vanessa; Marín, Francisco; Manzano-Fernández, Sergio; Fernández, Hermógenes; Gallego, Pilar; Valdés, Mariano; Vicente, Vicente; Lip, Gregory Y. H. (Thrombosis and Haemostasis, 2013)
Chronic Kidney Disease (CKD) constitutes an adverse risk factor in chronic anticoagulated atrial fibrillation (AF) patients, being related to adverse cardiovascular events, mortality and major bleeds. It is unclear if CKD adds independent prognostic information to stroke risk stratification schemes, as the risk factor components of the CHADS2 and CHA2DS2-VASc scores are themselves related to renal dysfunction. The aim of our study was to determine if CKD independently improves the predictive value of the CHADS2 and CHA2DS2-VASc stroke stratification scores in AF. We recruited consecutive patients (n=978) patients (49% male; median age 76) with permanent or paroxysmal AF on oral anticoagulants with acenocoumarol, from our out-patient anticoagulation clinic. After a median follow-up of 875 (IQR 706–1059) days, we recorded stroke/transient ischaemic attack (TIA), peripheral embolism, vascular events (acute coronary syndrome, acute heart failure and cardiac death) and all-cause mortality. During follow-up, 113 patients (4.82%/year) experienced an adverse cardiovascular event, of which 39 (1.66%/year) were strokes, 43 (1.83%/year) had an acute coronary syndrome and 32 (1.37%/year) had acute heart failure. Also, 102 patients (4.35%/year) died during the following up, 31 of them (1.32%/year) as a result of a thrombotic event. Based on c-statistics and the integrated discrimination improvement (IDI), CKD did not improve the prediction for stroke/systemic embolism, thrombotic events and all-cause mortality using the CHADS2 and CHA2DS2-VASc scores. In conclusion, evaluating renal function in AF patients is important as CKD would confer a poor overall prognosis in terms of thromboembolic events and all-cause mortality. Adding CKD to the CHADS2 and CHA2DS2-VASc stroke risk scores did not independently add predictive information.Note: The review process for this manuscript was fully handled by Christian Weber, Editor in Chief.
Keywords: Atrial fibrillation; chronic kidney disease; stroke; mortality